Reformas estructurales : mitos y realidades - Monreal Ávila, Ricardo, 1960- (México, D.F. : Cámara de Diputados, LXII Legislatura : Miguel Angel Porrúa, 2014)
Sharply critical analysis of Mexico's recent round of ambitious structural reforms, particularly of oil industry and finance reforms, which author says show direct line of descent from 18th-century Bourbon reforms, politics of Porfirio Diaz and neoliberal ideals of Carlos Salinas de Gortari, historical antecedents vilified by many on left in Mexico. Author was Mexico's youngest elected governor and is currently serving in Congress.
Introducción -- México antes del neoliberalismo -- El Consenso de Washington y sus predecibles efectos -- Cuatro ciclos de reformas estructurales en México -- El desarrollo estabilizador mexicano vs. el "milagro chino" -- Un plan de modernizaciâon para México -- Reflexiones finales.
Incluye referencias bibliográficas (páginas 265-272).
Descripción basada en recurso en línea; Título de la página del título en PDF (e-libro, visto June 08, 2015).
Recurso electrónico. Santa Fe, Arg.: e-libro, 2015. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a e-libro.
Keywords: Ajuste estructural -- México.; Neoliberalismo -- México.; Structural adjustment (Economic policy) -- Mexico; Neoliberalism -- Mexico; Libros electrónicos.